Pengembangan Religious Culture melalui Manajemen Pembiasaan Diri Berbasis Multikultural - Tola, Ardianto; Daeng Pawero, Abdul Muis; Tabiman, Nia Hariyati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Religious Culture is an important religious culture that belongs to every human being, especially students. Because students are very vulnerable to the name of religious differences. Especially in a public school that has students with a variety of religions. This difference is sometimes a problem between religious groups. This study discusses the Development of Religious Culture in Junior High School 2 Tomohon. To further narrow the research, the researchers used the research process through Self-habituation Management conducted by the school. This study used a descriptive qualitative approach with locations in Junior High School 2 Tomohon. The research subjects were Religious Teachers, while the research Informants were Principals, Religion Teachers, and 7th and 9th Grade Students. The research method used was carried out through interviews, observation, and documentation. While the data validity technique uses triangulation methods and sources. The results of this study conclude that planning a religious culture development based on self-habituation management that comes from management functions namely Planning, Organizing, Actuating, Controling. Self-habituation management is to change the behavior of students who are carried out continuously so that they can be changed according to expectations. To implement Religious Culture at Junior Hugh School 2 Tomohon must have a definite goal so that its implementation runs effectively. The application carried out in schools is by small things such as greeting one another, no mockery of mockery, mutual respect, and mutual assistance. Thus, this application does not create a burden to students in Junior High School 2 Tomohon.